Identity in Africa / African identity! Bloom, L (1998) Identity and ethnic relations in Africa. Aldershot: Ashgate. ISBN 1-84014-529-3. - Durrheim, Kevin (PINS-Psychology in Society, 2026)
I am probably not the best person to review Len Bloom’s collection of essays. Although I share with him an interest in identity and social relations in Africa, we come from different worlds: geographically, theoretically, and generationally. At times I was astounded by the vigour of Bloom’s political commitment to freedom and the manner in which he translated this politics into his everyday life. I found a companion social psychologist who insists on a political and politicised psychology. At the same time, I found myself baulking at some of his arguments, whose humanism and universalism seemed to be of a previous age.